2021
DOI: 10.1021/acs.jnatprod.1c00188
|View full text |Cite
|
Sign up to set email alerts
|

Proharziane and Harziane Derivatives from the Marine Algicolous Fungus Trichoderma asperelloides RR-dl-6-11

Abstract: One new proharziane and three new harziane derivatives (1−4) together with six known ones (5−10) were isolated from the marine-alga-derived ascomycete Trichoderma asperelloides RR-dl-6-11. Their structures and relative configurations were determined via spectroscopic techniques, and the absolute configurations were ascertained by analysis of ECD curves. This is the first report on the secondary metabolites of T. asperelloides, and the new isolates (1−4), especially seco-harziane 4, greatly add to the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…These new secondary metabolites, including terpenoids, alkaloids, polyketides, peptides, and steroids, exhibited high structural diversity and various bioactivities, such as antimicrobial, antifungal, cytotoxic, antioxidative, and enzyme-modulatory properties [3][4][5]. Terpenoids not only widely exist in the genus Trichoderma that from medicinal plants [6,7], but make up the largest proportion of new secondary metabolites produced by algicolous Trichoderma [4,[8][9][10][11][12][13][14]. Our previous chemical investigation of T. brevicompactum A-DL-9-2 resulted in the identification of eight new trichothecene sesquiterpenoids, trichodermarins G-N, and two new cuparene derviatives, trichocuparins A and B [14].…”
Section: Introductionmentioning
confidence: 99%
“…These new secondary metabolites, including terpenoids, alkaloids, polyketides, peptides, and steroids, exhibited high structural diversity and various bioactivities, such as antimicrobial, antifungal, cytotoxic, antioxidative, and enzyme-modulatory properties [3][4][5]. Terpenoids not only widely exist in the genus Trichoderma that from medicinal plants [6,7], but make up the largest proportion of new secondary metabolites produced by algicolous Trichoderma [4,[8][9][10][11][12][13][14]. Our previous chemical investigation of T. brevicompactum A-DL-9-2 resulted in the identification of eight new trichothecene sesquiterpenoids, trichodermarins G-N, and two new cuparene derviatives, trichocuparins A and B [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of our previous bioassays (Miao et al 2012;Liang et al 2020;Shi et al 2021;Zou, Song, Zeng, et al 2021), the inhibition of marine phytoplankton species (Chattonella marina, Heterosigma akashiwo, and Prorocentrum donghaiense) by compound 1 was evaluated. The results showed that 1 inhibited the three phytoplankton species with IC 50 values being 13, 29, and 2.8 lg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1 was assayed for the antimicroalgal activity against the marine phytoplankton Chattonella marina, Heterosigma akashiwo, and Prorocentrum donghaiense and was assayed for the antibacterial activity against the marine-derived bacteria V. anguillarum, V. parahaemolyticus, V. harveyi, and V. splendidus, using the methods that were described previously (Miao et al 2012;Zou, Song, Zeng, et al 2021). CuSO 4 and chloramphenicol were used as positive controls for antimicroalgal and antibacterial assays, respectively.…”
Section: Bioassaymentioning
confidence: 99%
“…Many of them showed various biological activities, including antimicrobial ( Shi et al, 2020 ), antimicroalgal ( Zou et al, 2021a ), antioxidant ( Miyano et al, 2020 ), antifouling ( Yu et al, 2021 ), anti-hepatitis C virus (HCV) ( Li B. et al, 2019 ), and cytotoxic activities ( Liu et al, 2020 ), implying the potential of Trichoderma species as a source of drugs for agricultural and/or human uses. Some Trichoderma species have been commercialized as agents to control phytopathogenic fungi or stimulate plant growth ( Morán-Diez et al, 2021 ; Zou et al, 2021b ). Here, we report the isolation, structure characterization, anti-PF activity, and cytotoxicity of secondary metabolites isolated from the deep-sea fungus Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%